Adverse Obstetric Outcomes Associated With In Vitro Fertilization in Singleton Pregnancies: A Prospective Cohort Study. (April 2017) - Qin, Jiabi; Sheng, Xiaoqi; Wu, Di; Gao, Shiyou; You, Yiping; Yang, Tubao; Wang, Hua
Objective: To compare the obstetric outcomes of women treated with in vitro fertilization (IVF), women with indicators of subfertility but without assisted reproductive technologies, and fertile women with singleton pregnancies. Methods: A prospective cohort study was conducted from March 2013 to February 2016 at the Hunan Provincial Maternal and Child Health Hospital in China. Finally, 1260 eligible mothers were recruited into the IVF group, 1899 into the subfertile group, and 2480 into the fertile group. Results: Compared to the fertile group, gestational diabetes mellitus (adjusted odds ratio [aOR] = 2.36; 95% confidence interval [CI]: 1.67-3.34), pregnancy-induced hypertension (aOR = 2.23; 95% CI: 1.37-3.64), placenta previa (aOR = 4.11; 95% CI: 2.12-7.96), premature rupture of membranes (aOR = 4.60; 95% CI: 2.71-7.81), anemia in pregnancy (aOR = 2.17; 95% CI: 1.42-3.31), preterm birth (PTB; aOR = 2.19; 95% CI: 1.59-3.02), low birth weight (aOR = 2.82; 95% CI: 2.02-3.94), perinatal mortality (aOR = 2.72; 95% CI: 1.67-4.03), and congenital malformations (aOR = 6.07; 95% CI: 3.14-11.72) were evidently increased in the IVF group, while placenta previa (aOR = 1.67; 95% CI: 1.05-2.67), PTB (aOR = 1.31; 95% CI: 1.05-1.64), low birth weight (aOR = 1.42; 95% CI: 1.12-1.81), and congenital malformations (aOR = 2.03; 95% CI: 1.28-3.21) were also increased in the subfertile group. Additionally, the IVF group compared to the subfertile group was at a higher risk of gestational diabetes mellitus (aOR = 1.40; 95% CI: 1.08-1.83), premature rupture of membranes (aOR = 1.45; 95% CI: 1.00-2.10), PTB (aOR = 1.26; 95% CI: 1.01-1.58), low birth weight (aOR = 1.75; 95% CI: 1.36-2.24), perinatal mortality (aOR = 1.95; 95% CI: 1.02-3.46), and congenital malformations (aOR = 1.81; 95% CI: 1.12-2.92). Conclusion: An increased risk of adverse outcomes in IVF pregnancies may be a result of the IVF procedures themselves and the infertility itself together.